Mechanical smart cleaning table. Issue 6 (January 2021) - Duan, Jinhong; Gan, He; Yu, Quanzhang; Chen, Yun
Abstract: Smart home is the inevitable development trend of future home furnishings. As an integral part of the home system, the dining table is bound to face a qualitative leap. As people yearn for a better, more comfortable and convenient life, the development of the dining table will become more intelligent and humanized. At present, people have a great demand for a variable dining area, and hope to avoid the tedious cleaning of the table after eating, and desire to be free from housework. Based on the above background, the team members designed a new type of self-cleaning dining table-mechanical intelligent cleaning dining table. The dining table has the characteristics of ingenious structure, diverse functions and stable performance, including three functional modules: folding and extending, table cleaning, and garbage collection. The ingenious cooperation between the various institutions can realize the folding and extension of the dining table, table cleaning and garbage collection functions. The mechanical intelligent cleaning table saves people's time, facilitates people's lives, and has high practical value and promotion value.